The Role of Supply Chain Finance in Improving SME Performance - Ivan Yulianto; Mohammad Nurkhamid; Marsanto Adi Nurcahyo (Universitas Sebelas Maret, 2025)
Supply Chain Finance (SCF) has become a strategic mechanism to improve the financial performance of small and medium-sized enterprises (SMEs), especially in the export sector. This study aims to examine the implementation and impact of SCF schemes on SMEs in Indonesia. Using a qualitative case study approach with semi-structured interviews and field observation, the research focuses on PT Asia Sejahtera Mina—a seaweed export company that serves as an anchor for various SME suppliers across the country. The findings show that SCF schemes implemented through pre- and post-shipment financing by Indonesia Eximbank (Lembaga Pembiayaan Ekspor Indonesia - LPEI) significantly improve SMEs’ cash flow, inventory turnover, and collection efficiency. Financial performance indicators such as Days Sales Outstanding (DSO), Days Payable Outstanding (DPO), Days Inventory Outstanding (DIO), Days Working Capital (DWC), and Cash Conversion Cycle (CCC) showed marked improvements post-SCF implementation. This study highlights the essential role of public financial institutions like LPEI in enabling SME access to structured finance and recommends the nationwide expansion of SCF schemes to improve SME competitiveness and economic inclusion.Keywords: financial performance; Indonesia eximbank; pre-shipment financing; post-shipment financing; smes; supply chain finance